Stereo- and Regioselective Synthesis of 2-Amino-3,5-diols via Stereospecific Crotyl Transfer and Regioselective Aminohydroxylation - McDonald, Frank E.; Pereira, Claney L. (Synthesis, 2012)
A short synthesis of 2-amino-3,5-diols is described, including the all-S isomer enigmol, a synthetic anticancer compound inspired by the structure of fumonisin B1. The synthetic route features 1) stereospecific crotyl transfer to tetradecanal via pericyclic oxonia-Cope rearrangement; 2) stereoselective epoxidation of the alkene; 3) regioselective epoxide opening with azide; and 4) reduction of azide to amine. This manuscript also corrects a structure assignment error in a previously reported synthesis of one of the diastereomers of enigmol.
Keywords: allylation; rearrangement; regioselectivity; sphingolipids; stereoselective synthesis